SCLEROTHERAPY PLUS OCTREOTIDE VERSUS SCLEROTHERAPY ALONE IN THE MANAGEMENT OF GASTRO-OESOPHAGEAL VARICEAL HEMORRHAGE - Shah, Hasnain A.; Mumtaz, Khalid; Jafri, Wasim; Abid, Shahab; Hamid, Saeed; Ahmad, Ashfaq; Abbas, Zaigham (Journal of Ayub Medical College Abbottabad, 2005)
Background: There are different ways for controlling oesophageal variceal bleed which include pharmacological and endoscopic methods. In this study we compare efficacy of octreotide (50 ïg/hr for 48 hours) combined with sclerotherapy versus sclerotherapy alone in patients with acute bleeding from gastro-oesophageal varices (GOV). Methods: It was a randomized clinical controlled trial conducted at Aga Khan University Hospital, Karachi, from January1997 to December 1998. We evaluated the role of octreotide (50 ïg/hr for 48 hours) combined with sclerotherapy versus sclerotherapy alone in a total of 105 adult cirrhotic patients who had acute bleeding from GOV. Patients were assigned to receive octreotide plus sclerotherapy or sclerotherapy alone. Primary outcome measure was 5-day survival without rebleeding. The hospital stay in days and blood transfusion requirements were also compared in the combined treatment group versus sclerotherapy alone group. Results: Initial control of bleeding was achieved in 46/51 (90.2%) patients who received combined treatment compared to 41/54 (75.9%) patients (p=0.05) in sclerotherapy alone group. Rebleeding after the first 48 hours was less in the octreotide treated patients 2/46 vs. 8/41 patients (p=0.003). The octreotide treated patients had a better short term (5 days) survival without rebleeding 44/51 vs. 33/54 (p=0.003) and shorter hospital stay, 5.31 ± 3.87 days vs. 6.63 ± 3.86 (p=0.008) as compared to sclerotherapy alone group. The blood transfusion requirement was also less in the combined treatment group 3.88 ± 2.80 vs. 5.37 ± 3.15 units (p=0.002). Conclusion: 1) The combination of sclerotherapy and octreotide infusion over 48 hours is more effective than sclerotherapy alone in the treatment of acute variceal bleeding and prevention of early rebleed in cirrhotic patients. 2) It leads to shorter hospital stay and 3) less blood transfusion requirements. 4) Although early survival without rebleeding is improved, the overall mortality at the end of hospitalization period is similar in the two groups of treated patients. Key words: Varices, Esophageal, Sclerotherapy, Octreotide, Cirrhosis.